Pengembangan E-Modul Menggunakan Aplikasi 3D Pageflip Professional Materi Teks Biografi di Kelas X SMK Negeri 2 Alasa - Johaneslim Zalukhu; Lestari Waruwu; Mastawati Ndruru (Indo-MathEdu Intellectuals Journal, 2023)
The observation results obtained were that students tend to get bored studying using existing printed books. The purpose of this research is (1) to develop e-modules. (2) to determine the feasibility of the e-module (3) to determine the practicality of the e-module, (4) to determine the effectiveness of the e-module. The method used is ADDIE which has 5 stages consisting of analysis, design, development, implementation, and evaluation. Based on the results of research by validation by material experts, the first revision was 56%, the second revision was 75.8% and the third revision was 94.8%. The results of validation by linguists in the first revision were 71%, the second revision was 78% and the third revision was 100%. The results of validation by media experts in the first revision were 52%, the second revision was 73% and the third revision was 96%. The results of individual trials were 86.6%, small group trials were 90%, and field trials were 97%. The completeness results obtained at the final evaluation reached 98.5% completeness. So, it can be concluded that e-modules can be said to be feasible, practical, and effective as learning references. Researchers suggest that through e-module media students will be motivated to learn